Kayan 1: a Particle Board from Rice Husk - Suhardy, Daud; Shamsul Baharin, Jamaludin, Prof. Dr.; Che Mohd Ruzaidi, Mohd Ghazali, Prof. Madya; Mohd Nazry, Salleh; Farizul Hafiz, Kassim; Saiful Azhar, Saad; Tengku Nadzlan, Tengku Ibrahim; Wan Su, Haron; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr. (Malaysian Invention and Design Society (MINDS), 2010)
Suhardy Daud and his team won gold at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.